Uji Analisis Nikel Ore/Ni (Sampel Cek) Menggunakan Metode Press Pellet Berdasarkan Variasi Suhu Pengeringan, Waktu Pengeringan, dan Berat Sampel Timbangan Press - Suwendi Suwendi; Sinardi Sinardi (Syntax Corporation Indonesia, 2024)
The purpose of the study was to determine the changes in nickel levels as a result of the analysis on the variation in temperature and drying time as well as the weight of press pellet scale samples from one of the same sample types. This research method is in the form of an experiment with a factorial research design from analysis parameters in the form of MC percentage and nickel ore content of Ni element. The results of the analysis showed that drying at 105°C and 125°C achieved a constant MC during a heating time of 5 to 6 hours. Meanwhile, at a temperature of 145-185 degrees Celsius with an interval of 2-6 hours, the MC level has experienced a constant weight of 44.44%. At the same temperature treatment, which is 105oC, different constant times are obtained. This is influenced by the difference in weight between the two samples, namely in the AP/5 and AP/6 range of 0.360 grams, while AP ORI weighs 1.8 kg. The results of the Epsilon 4 reading showed that the variation in drying temperature at 105°C to 185°C and drying time of 3-6 hours affected the nickel ore content in the range of 1.50% to 1.53%, close to the standard value of nickel 1.50%. The lower the temperature and drying time, the humidity level of the sample increases, causing the nickel ore content to decrease, while the higher the temperature and drying time increases the risk of nickel decomposition. The optimum temperature and drying time is 165°C for 2-4 hours. The press sample weight is between 8-14 grams resulting in a stable nickel content at 1.47%-1.50%, with an optimum weight of 10-14 grams for optimal sample thickness and density.